ENGLISH WITH THE AUDIOVISUAL METHOD: EFFECTIVENESS OF ITS USE FOR DEAF STUDENTS - Akhmad Feri Fatoni; Iva Gamar Dian Pratiwi (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
This study aims to determine the effectiveness of audiovisual-based English content in improving the vocabulary of deaf students. The research method employed in this study is mixed methods (a combination of qualitative and quantitative approaches). First, the team will use a descriptive qualitative method with an in-depth interview approach to understand the teaching and learning process. Then, the research team will use a quantitative method, namely a quasi-experiment with a pre-posttest design, to determine whether audiovisual-based YouTube content can effectively improve the English vocabulary of deaf students. Based on the results of in-depth interviews, researchers obtained data that in teaching English to deaf students, teachers utilized concrete objects around the students and the memorization method. Meanwhile, based on the results of experiments using the Paired Sample Test, the calculated t value was negative (-16.263), which means that the average pretest score was lower than the post-test score. The sig. (2-tailed) value showed 0.000 < 0.005, indicating a significant difference in English learning outcomes using the audiovisual method for deaf students at SLB Negeri Saronggi.